Hubungan Usia, Frekuensi ANC, dan Dukungan Suami dengan Kecemasan Ibu Hamil Primigravida Trimester III Menjelang Persalinan - Dwi Nurhasanah; Helni Anggraini; Diah Sukarni (Universitas Batanghari Jambi, 2022)
Anxiety is a term that is very familiar with everyday life which describes a state of worry, anxiety, fear, accompanied by various physical complaints. Pregnant women are often filled with anxiety, especially for women who are pregnant for the first time, especially before the delivery process. The purpose of this study was to determine the relationship between age, frequency of ANC, and husband's support with the anxiety of third trimester primigravida pregnant women before delivery at PMB Greece Seberang Ulu I Palembang in 2021. The research design used an Analytical Survey with a Cross Sectional approach. The population in this study were primigravida third trimester pregnant women totaling 110 people. The sampling technique in this study was carried out by purposive sampling with a total sample of 52 respondents. Data collection using a questionnaire sheet. The results of the chi square statistical test showed that there was a relationship between age, ANC frequency and husband's support and anxiety in third trimester primigravida pregnant women before delivery.